Implementation of Flipped Classroom Learning Model to Increase Student’s Critical Thinking Ability - Putri, Yuliana; Cahyono, Edy; Indriyanti, Dyah Rini (Universitas Negeri Semarang, 2021)
Students must have critical thinking ability and utilize ICT in the learning process to face the challenges of 21st century learning. Likewise, in biology learning accompanied by contextual learning related to everyday life such as the concept of environmental change. Technological developments also need to be maximally utilized in the learning process by flipped classroom learning. This study aims to know the increase in students' critical thinking ability towards flipped classroom learning model. This research method used a quasi-experimental design with a non-equivalent pretest posttest control group design. The subjects of this study included students of class XMIPA 1 and XMIPA 2 at SMAN 1 Palimanan. The results showed that there is a difference in the increase in critical thinking ability between the experimental class and the control class. The experimental class has a higher N-gain than the control class. The independent sample T test hypothesis test shows that the N-Gain significance value is less than the alpha value, which means that there is a significant difference in critical thinking skills between the experimental class and the control class. Based on the research conducted, it can be concluded that flipped classroom learning can increase students' critical thinking ability in environmental change material.